Anti‐windup scheme based on 2DOF‐PIλDμ controller for velocity tracking of linear induction motor. (10th July 2019) - Saleh, Ameer L.; Obed, Adel A.; Al‐Yasir, Yasir I. A.; Elfergani, Issa T. E.; Rodriguez, Jonathan; Clarke, Roger W.; Abd‐Alhameed, Raed A.
Summary: Recently, a new scheme of conventional PID (Proportional Integral Derivative) controller has been utilized in different electrical drives for speed control. This paper presents an optimal P I λ D μ controller with 2DOF and anti‐windup techniques based on PSO optimization to produce the proposed controller which is exploited in order to control the velocity control of LIM. A three‐phase inverter with SVPWM technique that is depended on approach of IFOC method is exploited to obtain the necessary output voltage supplied to the main windings of the LIM in order to control the velocity with minimum harmonics and good characteristics. The end effect is taken into account in dq axis equivalent circuit. Computed investigations show that the proposed controller is efficient in improving motor performance.